(untitled) (Research, Society and Development, 2020)
This paper aims to discuss the data for monitoring the water quality of the Paraopeba River and the collection of water for human consumption located on its banks, carried out by the Minas Gerais Water Management Institute - IGAM and by the Minas Gerais State Health Department - SES -MG after the rupture of the B1 dam of the Córrego do Feijão mine, under the responsibility of the company VALE SA (Brumadinho - MG), which occurred on January 25, 2019. In addition to the lost human lives and great impact on the environment, a mud it reached several sources of water for public supply, in addition to impacting the family income of several riverside dwellers who use river water for agriculture and animal feed. IGAM’s monitoring data points to violations of the parameters of turbidity, dissolved iron, total manganese and dissolved aluminum throughout the monitored period; total lead and copper dissolved in the rainy season, and also zinc, mercury and nickel in the first quarter of the monitoring. The monitoring data from SES-MG, on the other hand, point to violations related to antimony, arsenic, barium, chromium, lead, mercury, and selenium, in addition to aluminum, iron and manganese. In view of the results presented in both monitoring, it is suggested to maintain the suspension of water use in the Paraopeba River and capture close to its banks for any use, in addition to the inheritance of the monitors, which is subsidiary in the decision-making by users.